Seismic Performance of Recycled Concrete Filled Circular Steel Tube Columns - Xu, Dingyi; Chen, Zongping; Zhou, Chunheng (Frontiers in Materials, 2020)
This study was conducted to experimentally investigate the behavior of recycled concrete-filled circular steel tube (RCFST) columns subjected to cyclic loading. Ten specimens were prepared and tested. Four parameters were used to characterize seismic behavior: the replacement percentage of recycled coarse aggregate (RCA), slenderness ratio, axial compression level, and steel ratio. A novel calculation method for the bearing capacity for RCFST columns is established. The failure processes and modes of RCFST columns are found to be similar to normal concrete-filled steel tube (CFST) columns. Varying the replacement percentage of RCA has little effect on the hysteresis curves of the RCFST columns. The RCFST columns also show seismic performance similar to that of CFSTs. The displacement ductility of all specimens is larger than 3.0 and the equivalent viscous damping coefficients corresponding to the ultimate load range from 0.305 to 0.460.